Pembangunan Instalasi Cuci Tangan dalam Menurunkan Risiko Penyebaran Covid-19 di TPA Km. 14 Kota Palangka Raya - Novrianti Novrianti; Nani Apriyani; Achmad Imam Santoso; Dhymas Sulistyono Putro (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Scavengers have a risk of contracting Covid-19, which comes from the garbage when it is sorted. Based on this, it is necessary to make efforts to build a handwashing installation in the Km. 14 Landfill Palangka Raya City environment to prevent Covid-19, for the convenience of scavengers at work without the need for worries. The handwashing installation placement is based on the points that scavengers frequently pass so that it will be easier to access. This easy access will increase handwashing installations, which will potentially reduce the risk of Covid-19 spreads in the Km. 14 Landfill Palangka Raya City. The 250 L reservoir is placed on a wooden support. The placement is intended to facilitate the installation of water taps and when washing hands. The installation of water faucets is carried out in the 250 L reservoir provided by the 250 L reservoir producer. The sink is placed just below the water faucet outside, making it easier to wash hands and regulate water flow. The water flow from the collected hand washing will then flow gravitationally to the water filter that has been attached to the hose for further filtering so that when it flows into the country, the results of handwashing will not reduce the quality of the soil or groundwater.